2008
DOI: 10.1080/14616730701868613
|View full text |Cite
|
Sign up to set email alerts
|

Attachment organization in Vietnam combat veterans with posttraumatic stress disorder

Abstract: Attachment organization in a combat-related PTSD sample was investigated and compared with previously published clinical and non-clinical samples. The association between insecure attachment and unresolved mourning classification (U-loss) and between U-loss and PTSD symptoms was investigated. Vietnam combat veterans diagnosed with PTSD and in treatment (N = 48) were administered the Adult Attachment Interview, the SCID-IV, and CAPS. The PTSD sample was like non-clinical samples in the incidence of secure attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This finding is consistent with prior research (Ein-Dor et al 2010;Renaud 2008), but also suggests an additional hypothesis to evaluate in future studies: whether avoidant attachments towards partner prevented trauma processing or if combat exposure fundamentally changed ones attachment to partner behaviors to align with avoidance. There were no significant correlations between any of the three secure attachment scales and PTSD severity, which also supports previous research on the relationship between secure attachment and PTSD with veterans (Harari et al 2009;Nye et al 2008). Additionally, there were no significant correlations between PTSD symptoms and the father attachment scales, which is consistent with the attachment literature that shows that mother attachments are generally more predictive than father attachments (see Cassidy and Shaver 2008 for several examples of this).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with prior research (Ein-Dor et al 2010;Renaud 2008), but also suggests an additional hypothesis to evaluate in future studies: whether avoidant attachments towards partner prevented trauma processing or if combat exposure fundamentally changed ones attachment to partner behaviors to align with avoidance. There were no significant correlations between any of the three secure attachment scales and PTSD severity, which also supports previous research on the relationship between secure attachment and PTSD with veterans (Harari et al 2009;Nye et al 2008). Additionally, there were no significant correlations between PTSD symptoms and the father attachment scales, which is consistent with the attachment literature that shows that mother attachments are generally more predictive than father attachments (see Cassidy and Shaver 2008 for several examples of this).…”
Section: Discussionsupporting
confidence: 90%
“…Whereas one study found a relationship between secure attachment style and fewer PTSD symptoms in active duty service members (Escolas et al 2012), other studies did not find relationships between secure attachment and PTSD (Harari et al 2009;Nye et al 2008). Using the Adult Attachment Interview (AAI; see Hesse 1999) with Vietnam veterans, Nye et al (2008) found no differences in level of secure attachment with veterans diagnosed with PTSD compared to those not diagnosed with PTSD. Instead, the authors found that unresolved/ disorganized AAI scores related to the trauma loss (referencing the combat experience) were related to more PTSD avoidance and numbing symptomatology.…”
mentioning
confidence: 95%
“…The unresolved classification was associated with the presence of a PTSD diagnosis in a sample of Dutch veterans (Harari et al, 2009), as well as with a greater likelihood of comorbid anxiety and PTSD in a sample of Vietnam combat veterans (Nye et al, 2008). Finally, among women with a history of childhood abuse, unresolved states of mind were associated with more comorbid anxiety disorders and with increased likelihood of a PTSD diagnosis, specifically (Stovall-McClough & Cloitre, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This includes studies of depression (Cole-Detke & Kobak, 1996;Rosenstein & Horowitz, 1996), bipolar disorder (Morriss, van der Gucht, Lancaster, & Bentall, 2009), eating disorders (Tasga & Balfour, 2014), substance use (Schindler & Browning, 2015), and per-sonality disorders (Fonagy et al, 1996). Interestingly, while some studies of PTSD (Woodhouse, Ayers, & Field, 2015) demonstrate similar results, other studies with combat veterans reveal high levels of security relative to childhood events in a three-way classification despite high levels of symptoms (Nye et al, 2008). …”
Section: Relationship To Dsm Conceptsmentioning
confidence: 84%